Namibia in history junior secondary history book - Mbumba, Nangolo; Noisser, Norbert H. (Zed Books u.a., 1989)
A textbook discussing the African country's precolonial past and colonial present as it struggles for selfdetermination. Includes study activities.
Keywords: Geschichte; Namibia; Namibia -- History; Schulbuch